2007
DOI: 10.1128/iai.01244-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Urease Operon of Brucella abortus and Assessment of Its Role in Virulence of the Bacterium

Abstract: Most members of the genus Brucella show strong urease activity. However, the role of this enzyme in the pathogenesis of Brucella infections is poorly understood. We isolated several Tn5 insertion mutants deficient in urease activity from Brucella abortus strain 2308. The mutations of most of these mutants mapped to a 5.7-kbp DNA region essential for urease activity. Sequencing of this region, designated ure1, revealed the presence of seven open reading frames corresponding to the urease structural proteins (Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 43 publications
(29 reference statements)
3
122
0
4
Order By: Relevance
“…In order for proper assembly of the urease metallocenter, all four of the accessory proteins must be functional. Although urease has been demonstrated to be an important virulence factor in a number of bacteria, such as Helicobacter pylori (11), Yersinia enterocolitica (10), Proteus mirabilis (9), Brucella species (1,45), and Klebsiella pneumoniae (27), the role of urease in EHEC pathogenesis is not defined. It is possible that, like some other bacteria, EHEC exploits the enzyme urease as an additional factor to aid with surviving the low pH conditions as it passes through the stomach.…”
mentioning
confidence: 99%
“…In order for proper assembly of the urease metallocenter, all four of the accessory proteins must be functional. Although urease has been demonstrated to be an important virulence factor in a number of bacteria, such as Helicobacter pylori (11), Yersinia enterocolitica (10), Proteus mirabilis (9), Brucella species (1,45), and Klebsiella pneumoniae (27), the role of urease in EHEC pathogenesis is not defined. It is possible that, like some other bacteria, EHEC exploits the enzyme urease as an additional factor to aid with surviving the low pH conditions as it passes through the stomach.…”
mentioning
confidence: 99%
“…While the T4SS is required for intracellular survival and replication, defects in LPS structure that eliminate O antigen result in a number of phenotypes, including sensitivity to complement-mediated killing, increased sensitivity to killing by antimicrobial peptides, increased maturation of dendritic cells, and attenuation in tissue culture and animal infection models (9,25,31). Recent studies have demonstrated a potential role of urease and bile salt hydrolase in oral infection by Brucella abortus and Brucella suis in mice (4,18,52). However, the roles of T4SS and LPS during B. melitensis infection via the digestive tract are not known.…”
mentioning
confidence: 99%
“…RD1 is located within the ORF BMEI1651, which encodes the urease accessory protein UreE1, leading to an in-frame deletion of His149-Gly157. Most members of the genus Brucella show strong urease activity [22], and it has been suggested that urease protects Brucella during their infection via the oral route, which is the major route of infection leading to human brucellosis [22]. Blat search analysis revealed a similar RD in B. canis and B. suis 1330.…”
Section: Resultsmentioning
confidence: 99%